Characterization and Quality Improvement of Organic Compost Using Geothermal Brine from PT Pertamina Geothermal Energy - Permana, Indra; Nirwanto, Yogi; Ismawati, Iis; Nuriansyah, Rifan; Rahmawati, Gina; Ardian Pratama, Nata; Fadhlurrahman A, Syafiq; Nur Fadila, Azzahra (Universitas Cokroaminoto Palopo, 2025)
Compost is an organic amendment capable of improving soil physical, chemical, and biological properties, yet its relatively low nutrient content often requires high application rates. This research aimed to evaluate the effects of different compost formulations enriched with geothermal brine on macronutrient composition and to identify the best compost–brine formulation that meets the nutrient requirements set by the Indonesian Ministry of Agriculture Regulation No. 261/2016. The study employed seven compost formulations with three replications, each supplemented with 20% geothermal brine, arranged in a randomized block design. Observed parameters included compost temperature and weight during decomposition, as well as total N, total P₂O₅, total K₂O, and total CaO content. The geothermal brine used in this study contained high concentrations of essential minerals, particularly potassium and calcium, along with relevant micronutrients such as boron. Formulations containing higher proportions of sheep manure exhibited rapid temperature increases in the initial phase, followed by faster stabilization, whereas grass-dominant mixtures decomposed more slowly due to higher lignin content and elevated C/N ratios. Among all treatments, formulation G (15% sheep manure, 60% grass, 20% coffee husk, 2.5% dolomite, and 2.5% zeolite) produced the highest levels of macronutrients—N, P, K, and Ca—surpassing other formulations and aligning with compost quality standards. Overall, incorporation of geothermal brine effectively enhanced potassium and calcium levels across all compost mixtures